Kanzler: Der Patriarch - Konrad Adenauer - Deick, Christian; Knopp, Guido (Germany, 1999)
The film follows the chancellorship of Konrad Adenauer as fell the course of the Bonn democracy. None of his successors had such hard decisions to make, and no one exercised his power as autocratically as he did.
Verzio Film Festival Submission
Keywords: Documentary films